2019
DOI: 10.5897/ijpc2019.0570
|View full text |Cite
|
Sign up to set email alerts
|

Differential item functioning of the career aspiration scale within Arab context

Abstract: The aim of the study was to examine the psychometric properties and the differential items functioning of short version of Career Aspiration Scale (CAS) in a sample of 2700 of Omani high school students. The results of the total score of CAS showed acceptable internal consistency (Cronbach's α=0.67). An exploratory factor analysis yielded a support for nine items version identifying single construct. Differential item functioning (DIF) analysis confirmed that there were differences on five items concerning gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The results of factor analysis supported a one-factor solution suggesting that the scale did not capture the multi-dimensions of CAS that was proposed by Gray and O'Brien (2007) and Gregor and O'Brien (2016). The one-factor solution accounted for 27.22 in variance, which indicated that the scale had only one dominant factor in nine items (Al-Bahrani, Al-Lawati, Abu shindi, Bakkar & Alsiyabi, 2019;Al-Bahrani et al, 2020).…”
Section: Measurementsmentioning
confidence: 60%
“…The results of factor analysis supported a one-factor solution suggesting that the scale did not capture the multi-dimensions of CAS that was proposed by Gray and O'Brien (2007) and Gregor and O'Brien (2016). The one-factor solution accounted for 27.22 in variance, which indicated that the scale had only one dominant factor in nine items (Al-Bahrani, Al-Lawati, Abu shindi, Bakkar & Alsiyabi, 2019;Al-Bahrani et al, 2020).…”
Section: Measurementsmentioning
confidence: 60%
“…The research problem centers on delineating the career trajectories, job roles, and industry distributions of DEI practitioners in Australia, ultimately contributing to a more nuanced understanding of their contributions and challenges. Through an analysis of LinkedIn data and the application of descriptive statistics and visualizations, the research objective is to shed light on the diverse will offer a good idea of a realistic timeframe in which to complete goals, balanced with a realistic view of oneself (Al-Bahrani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%